Perbandingan Perilaku Struktur Gedung Beton Bertulang dengan Pelat Lantai Beton Konvensional dan Pelat Lantai Kalsi - Astariani, Ni Kadek; Sudika, I Gusti Made (Department of Civil Engineering, Diponegoro University, 2018)
The Structure of Reinforced concrete building using kalsi floor plate is one alternative for reduced the weight of the building structure. The floor plate usually used conventional concrete, can be replaced with kalsi floor 20. The aim of the research is to analysis of the behavior of reinforced concrete building using conventional concrete slabs and kalsi floor 20. The building structure as the model in this research is the building structure of four floors and was designed to follow the rules of SNI 2847: 2013. Evaluation of seismic behavior in accordance with the SNI 1726: 2012 was conducted out by applying pushover analysis using SAP 2000 software. The analysis results showed that drift ratio of plates floor structure models smaller than the kalsi floor plate structure. The pushover analysis results show the level of performance of all structural models according to FEMA-356 / ATC-40 able to provide nonlinear behavior which is indicated by the initial phase of the majority of plastic joints on beam elements and beam sway mechanism. The performance level of the structure with conventional concrete slab includes at immediate occupancy level, while the performance level of the structure with with kalsi floor plate includes at life safety level.